Effects of postpartum Trypanosoma vivax infection on feed intake, liveweight changes, milk yield and composition in West African Dwarf ewes and associated lamb growth rates - Akinbamijo, O.O.; Reynolds, L.; Sherington, J.; Nsahlai, I.V. (Cambridge University Press, 1994)
The effects of trypanosomiasis on digestible organic matter intake, milk yield and composition, dam liveweight changes during lactation and lamb growth rates were investigated at Ibadan, Nigeria 1991/92, using 20 West African Dwarf sheep nursing single lambs. Although digestibility coefficients were neither affected by infection nor by level of feed intake, organic matter intake during early and late lactation was significantly lower in infected animals due to reduced feed intake. Mean daily milk yields were not affected by the infection during early lactation; however, during the second half of lactation, average daily milk yields were significantly lower in infected animals than in uninfected controls. Variations in milk component concentrations between experimental groups did not attain statistical significance throughout lactation. While control ewes on a medium plane of nutrition (CH) gained 12.1 g/day, infected ewes (IH) and uninfected control ewes on a medium plane of nutrition (CM) lost 45 and 5.4 g/day respectively during lactation. Liveweight gain in the lambs was not affected by infection in the dams. This study demonstrated reduction in feed intake, late lactation milk yield and dam liveweight gain with no adverse effect on digestibility coefficients, mild composition, early lactation milk yield and lamb weight gain during T. vivax infection of lactation ewes.